A parallel-bonded chemical corrosion model for discrete element modelling of chemically corroded limestone. (15th October 2018) - Li, Hao; Eshiet, Kenneth Imo-Imo; Sheng, Yong; Zhong, Zuliang; Liu, Xinrong; Yang, Dongmin
Highlights: A parallel-bonded chemical corrosion (PCE) model for modelling corroded rocks (limestone) is developed. Nuclear Magnetic Resonance (NMR) and triaxial compression tests are carried to determine the damage law of the PCE model. The PCE model is implemented in Discrete Element Method (DEM) and calibrated by experiments. The PCE model is applied to investigate the chemical effects on crack propagation in rocks. Abstract: The mechanical behaviours of rock mass are influenced by the presence of cracks at the microscopic and macroscopic levels. When coupled with corrosion by chemical ions in ground water, these cracks can cause instabilities and fragmentation near the excavated surface of underground structures, such as shield tunnels, etc . This paper presents the development of a parallel-bonded chemical corrosion (PCC) model for modelling corroded rocks (limestone). The model extends the bonded-particle model (BPM) by adding a chemically induced damage law to the particle bond. The damage law of the PCC model is derived from Nuclear Magnetic Resonance (NMR) and triaxial compression tests. The PCC model is validated with experimental results and is capable of simulating the micro-damage evolution process as well as predicting the macro-mechanical degradation caused by the chemical corrosion. It is then applied to investigate chemical effects on crack initiation, propagation, coalescence, and the mechanical properties of the limestone containing pre-existing flaws. Microscale correlations are derived linking the crack propagation process, flaw distribution and the effects of chemical corrosion.